Analisis Altman Z-Score sebagai Alat Prediksi Dini Kebangkrutan: Studi Kasus pada PT Sri Rejeki Isman, Tbk (Lembaga Pengembangan Kinerja Dosen, 2025)
The textile and textile products (TPT) industry is one of the strategic sectors in the Indonesian economy with a significant contribution to Gross Domestic Product (GDP), employment, and national exports. In the first quarter of 2024, the manufacturing industry sector contributed 19.28% to national GDP, with the textile and apparel sub-sectors showing growth of 5.90% and 2.64% respectively year-on-year (yoy). However, this sector faces challenges in the form of global competition, illegal imports, and declining export volumes, which in 2023 reached their lowest point in the last nine years with a decline of 2.43%. In response, the government has tightened import policies, provided incentives, and reformed investment policies to attract more domestic and foreign investment. With these efforts, the TPT industry remains an important pillar of the national economy, although it requires further strategies to face challenges and ensure its sustainability. The type of data used in this study is secondary data that is quantitative in nature. The data needed is the annual financial report of PT ABC Tekstil Tbk from 2020-2024. The model used in this study is the Altman Z-Score model. This method is used to predict the risk of bankruptcy in a company. From the results of this study, it can be concluded that the analysis using the Altman Z-Score method at PT Sri Rejeki Isman Tbk, for the period 2020-2024 is in an unhealthy condition or in a Distress Zone condition and has quite serious financial problems.